Pentadal classification of wind off Peruvian coast - Correa, David (2020)
The wind off the Peru coast has influence on marine physical, chemical and biological processes, both in surface and sub-surface layers and impacts coastal sea currents, sea surface temperature, vertical mixing layer, transport and retention of larvae in the sea. Furthermore it influences the approach of oceanic waters towards the coast and in other cases it favors the extension of Cold Coastal Waters and Mixing Waters off the Peruvian coast through the coastal upwelling. Therefore, the intensification and weakening of coastal wind have a strong impact on environmental conditions and the ecosystem. In this work, satellite wind data obtained through the ASCAT (Advanced Scatterometer) scaterometer from a coastal strip up to 100 km (approximately 62 nautical miles) off Peru was used in five areas: Paita, Chicama, Callao, San Juan de Marcona and Ilo, during the period from March 21, 2007 to March 03, 2019, in order to analyze the intraseasonal variability of the wind and determine, based on the grouping of quartiles and moving averages, the minimum and maximum wind intensities for the identification of events of intensification or weakening respectively. The results show that the intra-seasonal wind variability is lower in the northern zone (Paita and Chicama), than in the central-southern zone (Callao, San Juan de Marcona and Ilo), which presents greater variability. The minimum and maximum pentadal intensities to identify wind intensification and weakening events showed different ranges of variation throughout the year and location along the Peruvian coast. Depending on the season, Ilo has minima wind intensities that vary between 2.1 to 3.8 ms-1 (weakening) and maxima between 4.4 to 5.2 ms-1 (intensification); while Paita, Callao and Chicama, have minimum wind intensities that vary between 2.3 to 4.8 ms-1 (weakening) and maxima between 4.2 to 7.3 ms-1 (intensification); while San Juan de Marcona has minimal wind intensities between 3.7 to 6.6 ms-1 (weakening) and maxima between 5.6 to 9.5 ms-1 (intensification). Finally, the number of days per year of wind intensification and weakening was determined, resulting in a predominance of wind intensification events during the years 2007, 2010 and 2013, and a predominance of wind weakening events during the years 2012, 2013, 2016 and 2017.